An Exploratory Study Investigating How Adults with Intellectual Disabilities Perform on the Visual Association Test (VAT). Issue 5 (5th August 2016) - McPaul, Ann; Walker, Brigid; Law, Jim; McKenzie, Karen
Abstract : Background: Neuropsychological tests of memory are believed to offer the greatest sensitivity at identifying people at the risk of developing dementia. There is a paucity of standardized and appropriate neuropsychological assessments of memory for adults with an intellectual disability. This study examines how adults with an intellectual disability perform on the Visual Association Test (VAT). Methods: Forty participants (18–45 years) with intellectual disability, without a diagnosis of dementia, completed the VAT and subtests of the CAMCOG‐DS. Correlational analysis of the test variables was carried out. Results: All participants performed well on the VAT irrespective of age, gender or IQ. No significant correlations were found between the VAT and the subtests of the CAMCOG‐DS. Conclusions: The VAT was found to be an easy and quick test to use with people with intellectual disability and all participants scored above 'floor' level.